Artefatos de contabilidade gerencial e maximização de valor em empresas de capital aberto do Brasil - Morais, Osvaldo de Oliveira (2011)
This research aimed to examine the existing relation between the implementation of managerial accountancy artifacts and maximization of value of publicly traded companies in Brazil, considering that value maximization depends on several factors, for instance, the implementation and use of managerial accountancy artifacts. These artifacts are meant to support managers, during their tasks, with financial and non-financial information. Given the challenging and competitive environment where companies operate, as well as constant changes and information diversification, guarantee assertiveness decision-making becomes a critical factor to company success. This research has adopted the quantitative approach and exploratory survey in order to achieve both the foundation as the methodological structure. To achieve the final goals, were employed both strategies the bibliography and the documentary survey. The research was conducted from 2000 until 2009, aimed to identify how artifacts implementation have evolved in later period of surveys conducted by consulted authors. The data about the surveyed companies were obtained at Economática, an agency that has access to financial information about publicly traded companies, in compliance with regulations and standards set by Brazilian Federal Reserve, known as Banco Central and the CVM, the Brazilian securities commission. In the meantime, the publicly traded companies listed at BM&FBOVESPA stock exchange filled out a questionnaire in order to reveal which managerial accountancy artifacts that have been used and their implementation date. Cause and effect relations were made between company segment groups, and well as the use evolution of managerial accountancy artifacts and value maximization. By applying statistical techniques of multiple linear regression as well as the adoption of the panel data, in order to compare and find out the existing relations between them. In sum, after investigations, it became evident through the hypothesis test that the managerial accountancy artifacts positively contributed to make decisions related to the conception of value-maximization. From the sample considered, results led to the recognition of the existence of relations between value maximization measured by the dimension of the highest operational performance, estimated by the return on Assets, and by implementation of managerial accountancy artifacts. The survey’s hypothesis could not be rejected, considering that the continual implementation of managerial accountancy artifacts meant to modernize managerial accountancy, contributes to maximize the surveyed companies operational performance. It is inferred that the artifact type, its modernness and up datedness tend to be more relevant than some amount of implemented artifacts.